THE SIGNIFICANCE OF LINGUISTIC APPROACH IN SHARḤ ḤADĪTH OF MIṢBĀḤ AL-ẒALĀM BY MUHAJIRIN AMSAR - Fatihunnada Fatihunnada; Nailil Huda; Hannanah Thabrani (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2022)
This paper strengthens the research of Shittu and Adebolu (2016) confirming that Arabic language science: semantics, naḥw-ṣarf, and balāghah has an important role in understanding ḥadīth. In addition, this research also strengthens Asmaʿ al-Khatab and Ali Younis affirming that the Arabic style of ḥadīth in terms of balāghah can provide a more comprehensive understanding of the historical facts of ḥadīth and the substance of ḥadīth teachings. In particular, this research concludes that Muhajirin Amsar (d. 2003) as one of the Indonesian ḥadīth experts has a deep concern about understanding ḥadīth with a language approach. This is proven by the study of semantics, naḥw-ṣarf, and balāghah in the Miṣbāḥ al-Ẓalām as a work that explains the legal ḥadīth of Islamic law.